Pengembangan Program Pelatihan Kewirausahaan dan Pendidikan Lingkungan di Sekolah ALQI Ceria Kota Bogor: Tinjauan Implementasi dan Dampaknya terhadap Kesadaran Kewirausahaan dan Kesadaran Lingkungan Siswa - Bahri, Asep Saepul; Herliana, Khotimah (Jurnal PKM Manajemen Bisnis, 2024)
This study aims to evaluate the implementation of entrepreneurship and environmental education training programmes at Alqi Ceria School in Bogor City and its impact on students' entrepreneurial awareness and environmental awareness. The research method used is a qualitative approach with in-depth interviews with teachers and students at the school. The results show that the training programme has successfully improved students' understanding of entrepreneurship and the environment and increased their interest in entrepreneurship and protecting the environment. This article concludes that the implementation of entrepreneurship and environmental education training programmes can be an effective strategy in increasing students' awareness of both areas.